Water quality studies of the main rivers that supply Semenyih dam / Norizan Mat Seman - Mat Seman, Norizan (2008)
A study of water quality, heavy metal concentrations and total coliform bacteria was conducted at four rivers supplying Semenyih Dam. The study areas include the edge of river mouth of Semenyih River, Kesuma River, Rephen River and Lanjut River. The methods used in this project were in-situ measurements and laboratory analysis. Water Quality Index (WQI) was determined using BOD track apparatus, YSI meter, HACH DRB 200, HACH DR 2010 spectrophotometer, and Ion Chromatograph (IC). The results were compared against Water Quality Index (WQI) and classification of water quality based on the Department of Organization Environment- Water Quality Index (DOEWQI). The results for the water quality of each river at Semenyih Dam was moderate that is in class III. For the heavy metals analysis, the analysis were conducted using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) and total coliform bacteria were determined by using membrane filtration. The results showed that the heavy metal concentrations is in class III and total coliform bacteria is in class I.